Artificial Intelligence in Language Teaching: Using ChatGPT to assist teachers of English as a Foreign Language - Salvatore Nizzolino (Firenze University Press, 2024)
This paper delves into the application of Artificial Intelligence (AI) to assist teaching practices through task-oriented dialogues. Specifically, it presents a practical implementation of ChatGPT in analyzing forum posts from two groups (n=30 and n=25) of first-year university students studying English as a Foreign Language (EFL). The experiment discloses the potential of AI in the field of education, particularly in linguistic-semantic evaluation, predictive analysis, and psychological profiling. In contrast, the free use of ChatGPT has limitations in the size of inputs it can analyze in a single interaction, while its accuracy and complexity remain unaffected in its unpaid version. The paper aims to provide a practical experience that can promote the further adoption of AI in education, along with guidelines for piloting its ethical application.   Intelligenza Artificiale e insegnamento delle Lingue: ChatGPT a supporto del docente d'Inglese Lingua Straniera. Il contributo affronta l'uso dell'Intelligenza Artificiale (IA) per assistere la pratica docente attraverso dialoghi task-oriented. In particolare, presenta l'utilizzo pratico di ChatGPT per analizzare post estrapolati dai forum didattici di due gruppi (n=30 e n=25) di studenti universitari al primo anno frequentanti corsi accademici d'inglese come lingua straniera. L'esperimento rivela le possibilità che l'IA offre nel campo dell'educazione, specificamente nella valutazione linguistico-semantica, nell'analisi predittiva e nel profiling psicologico. Per converso, l'uso gratuito di ChatGPT presenta alcune limitazioni nella dimensione degli input che può analizzare in un'unica interazione, mentre l'accuratezza e le capacità di analisi rimangono invariate nella versione non a pagamento. Il contributo mira a fornire un'esperienza pratica che può stimolare l'adozione dell'IA nel settore educativo, congiuntamente a idonee linee guida per un orientamento etico durante l'applicazione.